Congenital Vallecular Cyst Causing Airway Compromise in a 2-Month-Old Girl - Amal Faisal AlAbdulla (Case Reports in Medicine)
Congenital vallecular cyst is a rare entity and may present with acute airway obstruction. This is a case of congenital vallecular cyst presenting with airway compromise requiring immediate management. The epidemiology, pathogenesis, and clinical presentation of vallecular cysts are discussed as well as the diagnosis and management.